Analysis of the Relationship Between External Debt and Economic Growth in Iraq : An Empirical Study - Fouad Saleh , Ali; Saleh Salman al-kubaisy , Mohammed (Journal of Economics and Administrative Sciences, 2024)
Purpose: Measuring and analyzing the relationship between external debt and economic growth in Iraq. Theoretical framework: The research dealt with the external debt and its impact on economic growth in Iraq. Iraq is one of the countries that suffers from the problem of external debt and its use to finance consumer spending. The research problem can be formulated as the absence of specific standards to guide financial policy in Iraq, especially the optimal size of debt and how to spend the debt in a way that achieves economic growth. Design/methodology/approach: The research relied on the deductive inference method based on theoretical foundations, descriptive and quantitative analysis, and standard methods based on theoretical foundations to measure the relationship between external debt and oil revenues as an independent variable in enhancing economic growth as a dependent variable. Indicators, statistical methods, hypothesis testing, and measurement will be used. Findings: The analysis results confirmed the validity of the hypothesis, and there is a statistically significant relationship between the independent variables of external debt and oil revenues and the dependent variable of economic growth. Research, Practical & Social implications: We propose a future research agenda and highlight the management of external debt in a way that contributes to enhancing economic growth. Originality/value: The relationship between external debt and GDP loads for Iraq (2003-2023) still needs to be addressed by analyzing the causal relationship between external debt and GDP according to the modern methodology.